Revealing the secrets of a 2900-year-old clay brick, discovering a time capsule of ancient DNA - Arbøll, TP; Rasmussen, SL; de Jonge, N; Hansen, AH; Pertoldi, C; Nielsen, JL (Springer Nature, 2023)
The recent development of techniques to sequence ancient DNA has provided valuable insights into the civilisations that came before us. However, the full potential of these methods has yet to be realised. We extracted ancient DNA from a recently exposed fracture surface of a clay brick deriving from the palace of king Ashurnasirpal II (883–859 BCE) in Nimrud, Iraq. We detected 34 unique taxonomic groups of plants. With this research we have made the pioneering discovery that ancient DNA, effectively protected from contamination inside a mass of clay, can successfully be extracted from a 2900-year-old clay brick. We encourage future research into this subject, as the scientific prospects for this approach are substantial, potentially leading to a deeper understanding of ancient and lost civilisations.